The Impact of an Auditor's Initial Hypothesis on Subsequent Performance at Identifying Actual Errors* - HEIMAN‐HOFFMAN, VICKY B.; MOSER, DONALD V.; JOSEPH, JERRY A. (Contemporary Accounting Research, 1995)
Abstract. Previous work on hypothesis generation demonstrates that auditors tend to generate frequently occurring financial statement errors as their initial hypotheses to explain unexpected fluctuations. However, such work does not examine how the initially generated hypothesis affects subsequent performance at identifying an actual error. We hypothesized that the initially generated hypothesis would interfere with an auditor's ability to subsequently switch to a different hypothesis. Thus, if the initial hypothesis were incorrect, auditors would find it difficult to switch hypotheses in order to identify an actual error. Moreover, initially generating a frequent error would exacerbate this difficulty. Auditor‐subjects were asked to generate an initial error hypothesis after seeing a pattern of fluctuations in which sales and accounts receivable were overstated. After they generated their initial hypothesis, half of the subjects were provided with additional information that was consistent with a very frequent error (sales cutoff) and the other half were provided with information consistent with an infrequent error (sales recorded twice). As expected, we found that initially generating the very frequent error (i.e., sales cutoff) versus some other less frequent error affected auditors' subsequent performance at identifying actual errors. Specifically, auditors who generated the very frequent error as their initial hypothesis performed best when it was the actual error, but performed worst when the infrequent error was the actual error. In contrast, auditors who generated a less frequent error as their initial hypothesis performed moderately well (i.e., between best and worst) both when the actual error was frequent and when it was infrequent. The implications of these results for audit efficiency and effectiveness are discussed.